Association of maternal dietary patterns, stress levels, and physical activity during pregnancy with stunting among children under five in brebes regency - Chyntia Olyvia Rizki Herwianti; Oktia Woro Kasmini Handayani; Sofwan Indarjo (Science Midwifery, 2026)
Stunting remains a major public health nutrition problem in Indonesia, particularly in Brebes Regency, which has one of the highest stunting prevalences in Central Java Province. Stunting can originate during the prenatal period and is influenced by maternal lifestyle factors during pregnancy. This study aimed to analyze the relationship between maternal lifestyle during pregnancy—including dietary patterns, physical activity, and stress levels—and the incidence of stunting among children aged 24–59 months in Brebes Regency. A case–control study design was employed involving 144 respondents (72 mothers of stunted children and 72 mothers of non-stunted children) selected from several public health centers. Data were collected through structured interviews using validated questionnaires and analyzed using bivariate analysis and logistic regression. The results showed that maternal dietary patterns, stress levels, and physical activity during pregnancy were significantly associated with stunting incidence. Mothers with unbalanced dietary patterns had a higher risk of having stunted children (OR = 2.87; p = 0.002). Similarly, moderate–high maternal stress (OR = 2.54; p = 0.004) and inappropriate physical activity (OR = 2.39; p = 0.006) were significantly associated with increased odds of stunting. Maternal lifestyle during pregnancy plays a crucial role in determining child growth outcomes. Therefore, stunting prevention strategies should prioritize prenatal interventions through improved nutritional education, stress management, and promotion of safe physical activity for pregnant women.